"The lissome lady from Spain": building Canadian modernism and flamenco dance in performance archives. Issue 3 (2nd September 2022) - Murphy, Emily Christina; McLeod, Katherine
ABSTRACT: This article recovers the training and early career of Barbara Mary Beck "Conchita Triana" (1912–2006), the first professional flamenco dancer in Canada, whose professional career spanned from 1938 into the late 1950s. This recovery entails an exploration of archival records, analysis of the role of Spain for modernist Canadian artists across disciplines, performance histories of Canadian, American, and Spanish artists, and close reading of archival dance notation. Together, these contexts allow us to analyze the construction and emergence of a Canadian settler identity in the 1930s alongside a home-grown Canadian flamenco dance. Performance of an ostensible exotic import – on the stage and through the appropriation of Spanish identity – reinforces the legitimacy of white settler identity through the "mosaic" metaphor that dominates 1920s and 1930s conceptualization of Canada, positioning itself for the first time as a nation distinct from Britain. Spanish cultural performance as a tool to explore Canadian settler identity remains relevant today, as Canadian flamenco artists continue to interrogate their own national identities through the artform.